Hf-W chronology of the accretion and early evolution of asteroids and terrestrial planets - Kleine, T; Touboul, M; Bourdon, B; Nimmo, F; Mezger, K; Palme, H; Jacobsen, S; Yin, Q; Halliday, A (2009)
The 182Hf-182W systematics of meteoritic and planetary samples provide firm constraints on the chronology of the accretion and earliest evolution of asteroids and terrestrial planets and lead to the following succession and duration of events in the earliest solar system. Formation of Ca,Al-rich inclusions (CAIs) at 4568.3 ± 0.7 Ma was followed by the accretion and differentiation of the parent bodies of some magmatic iron meteorites within less than ∼1 Myr. Chondrules from H chondrites formed 1.7 ± 0.7 Myr after CAIs, about contemporaneously with chondrules from L and LL chondrites as shown by their 26Al-26Mg ages. Some magmatism on the parent bodies of angrites, eucrites, and mesosiderites started as soon as ∼3 Myr after CAI formation and may have continued until ∼10 Myr. A similar timescale is obtained for the high-temperature metamorphic evolution of the H chondrite parent body. Thermal modeling combined with these age constraints reveals that the different thermal histories of meteorite parent bodies primarily reflect their initial abundance of 26Al, which is determined by their accretion age. Impact-related processes were important in the subsequent evolution of asteroids but do not appear to have induced large-scale melting. For instance, Hf-W ages for eucrite metals postdate CAI formation by ∼20 Myr and may reflect impact-triggered thermal metamorphism in the crust of the eucrite parent body. Likewise, the Hf-W systematics of some non-magmatic iron meteorites were modified by impact-related processes but the timing of this event(s) remains poorly constrained. The strong fractionation of lithophile Hf from siderophile W during core formation makes the Hf-W system an ideal chronometer for this major differentiation event. However, for larger planets such as the terrestrial planets the calculated Hf-W ages are particularly sensitive to the occurrence of large impacts, the degree to which impactor cores re-equilibrated with the target mantle during large collisions, and changes in the metal-silicate partition coefficients of W due to changing fO2 in differentiating planetary bodies. Calculated core formation ages for Mars range from 0 to 20 Myr after CAI formation and currently cannot distinguish between scenarios where Mars formed by runaway growth and where its formation was more protracted. Tungsten model ages for core formation in Earth range from ∼30 Myr to >100 Myr after CAIs and hence do not provide a unique age for the formation of Earth. However, the identical 182W/184W ratios of the lunar and terrestrial mantles provide powerful evidence that the Moon-forming giant impact and the final stage of Earth's core formation occurred after extinction of 182Hf (i.e., more than ∼50 Myr after CAIs), unless the Hf/W ratios of the bulk silicate Moon and Earth are identical to within less than ∼10%. Furthermore, the identical 182W/184W of the lunar and terrestrial mantles is difficult to explain unless either the Moon consists predominantly of terrestrial material or the W in the proto-lunar magma disk isotopically equilibrated with the Earth's mantle. Hafnium-tungsten chronometry also provides constraints on the duration of magma ocean solidification in terrestrial planets. Variations in the 182W/184W ratios of martian meteorites reflect an early differentiation of the martian mantle during the effective lifetime of 182Hf. In contrast, no 182W variations exist in the lunar mantle, demonstrating magma ocean solidification later than ∼60 Myr, in agreement with 147Sm-143Nd ages for ferroan anorthosites. The Moon-forming giant impact most likely erased any evidence of a prior differentiation of Earth's mantle, consistent with a 146Sm-142Nd age of 50-200 Myr for the earliest differentiation of Earth's mantle. However, the Hf-W chronology of the formation of Earth's core and the Moon-forming impact is difficult to reconcile with the preservation of 146Sm-142Nd evidence for an early (<30 Myr after CAIs) differentiation of a chondritic Earth's mantle. Instead, the combined 182W-142Nd evidence suggests that bulk Earth may have superchondritic Sm/Nd and Hf/W ratios, in which case formation of its core must have terminated more than ∼42 Myr after formation of CAIs, consistent with the Hf-W age for the formation of the Moon. © 2009 Elsevier Ltd. All rights reserved.